2003
DOI: 10.1103/physrevlett.90.195504
|View full text |Cite
|
Sign up to set email alerts
|

First X-Ray Scattering Studies on Electrostatically Levitated Metallic Liquids: Demonstrated Influence of Local Icosahedral Order on the Nucleation Barrier

Abstract: To explain the unusual stability of undercooled liquids against crystallization, Frank hypothesized that the local structures of undercooled liquids contain a significant degree of icosahedral short-range order, which is incompatible with long-range periodicity. We present here the first direct experimental demonstration of Frank's complete hypothesis, showing a correlation between the nucleation barrier and a growing icosahedral short-range order with decreasing temperature in a Ti39.5Zr39.5Ni21 liquid. A new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
268
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(296 citation statements)
references
References 16 publications
27
268
1
Order By: Relevance
“…Unlike crystalline materials, MGs do not have long-range translational order. However, various experiments [3,4] and computer simulations [5,6] have revealed short-to medium-range order in MGs. Here we define the short-range order (SRO) restricted to atomic arrangement within the first coordination shell.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike crystalline materials, MGs do not have long-range translational order. However, various experiments [3,4] and computer simulations [5,6] have revealed short-to medium-range order in MGs. Here we define the short-range order (SRO) restricted to atomic arrangement within the first coordination shell.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal-liquid interfacial energy arises from configurational entropy differences between crystal and liquid phases. Pronounced differences in the local structural ordering between the crystal phase and the liquid phase lead to an increased interfacial energy and consequently to a higher nucleation barrier [1,2]. Experimental and theoretical studies indicated that the CNT might not be adequate for the description of the initial nucleation process [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray diffraction pattern (Bruker AXS, D5000, Cu K α1 radiation) revealed that the sample consisted of the α-modification (P2 1 ). Paracetamol ( ≥ 99% purity, Sigma-Aldrich) was used without purification.…”
Section: -Methyl-2-[(2-nitrophenyl)amino]-3-thiophenecarbonitrilementioning
confidence: 99%
“…However, since icosahedra cannot be packed without gaps, they are distorted and/or mixed with other AETs. Furthermore, not only in solids but also in undercooled metallic melts icosahedral short-range order may not be the exception (Kelton, 2003).…”
Section: Introductionmentioning
confidence: 99%